IMMIGRATION POLICY IN EFFORTS TO ERADICATION AND PREVENTION OF HUMAN TRAFFICKING - Fikri Madani Tara Putra; Anindito R. Wiraputra (Polteknik Imigrasi, 2020)
The large potential for transnational crime in Indonesia is a problem that needs to be addressed. In this case it is a problem of human trafficking, these problems are very complex and complicated to solve. This trafficking is usually aimed at children and women. There are so many modes used by these perpetrators, one of them is through sending illegal Indonesian Workers. The government began to move specifically in the field of immigration in carrying out efforts to combat human trafficking in violation of human rights, because immigration is the front guard in examining people who leave or enter Indonesian territory. Selective policy helps immigration parties in the Immigration Examination Site in selecting foreigners who enter the territory of Indonesia. And immigration also supervises the sending of Indonesian Workers abroad. This supervision is intended to avoid sendingillegal Indonesian Workers.